Pulsujące metafory dydaktyki w kleszczach języka. O lingwistycznych blokadach konstruktywistycznej zmiany w kształceniu - Astrid Męczkowska-Christiansen (Problemy Wczesnej Edukacji)
The content of the article includes analyses of the linguistic plane of the reception of constructivist didactics, carried out in order to seek a partial answer to the question: why does the paradigmatic change in the area of school education in Poland, which has been intensively postulated by scientific circles over the last thirty years, not materialise in the space of contemporary educational practices in their institutional settings? In particular, the subject of analyses refers to the dominant – “instructive” – linguistic level of general didactics, with regard to such concepts as: education, learning, knowledge. The purpose of the linguistic analyses was to show how the existing constellations of didactic metaphors have hindered the conceptualisation and reception of ideas coming from constructivist positions.